Republic of Palau : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Palau. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Palau's economy has performed well in recent years. The economy grew strongly in FY2015 (ending September 30, 2015) at 9.4 percent, with tourist arrivals and construction activity expanding by 35 percent. However, the rapid rise in tourism activity strained infrastructure and was tilted toward low budget tourists, which led the authorities to limit the number of charter flights in FY2016. The outlook for Palau is also favorable. Economic growth is expected to slow temporarily to zero in FY2016 as tourist arrivals decline, but to rebound to 5 percent in FY2017 as tourism activity recovers with the entry of new hotels and construction picks up.